1998
DOI: 10.1038/sj.leu.2400946
|View full text |Cite
|
Sign up to set email alerts
|

Serum thrombopoietin levels in patients correlate inversely with platelet counts during chemotherapy-induced thrombocytopenia

Abstract: We studied serum thrombopoietin (TPO) levels and circulating numbers of platelet during five courses of myelosuppressive post-remission chemotherapy in three patients with acute leukemia in complete remission. Serum TPO levels were measured by a newly developed and sensitive sandwich enzyme-linked immunosorbent assay. In all courses, serum TPO levels changed reciprocally with the platelet counts. When platelets were transfused into patients near the time of platelet nadir, the TPO levels dropped temporarily, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
2
40
1
1
Order By: Relevance
“…Because most of Mpl is expressed on platelets and megakaryocytes, plasma TPO levels fluctuate in response to the physiologic demand for megakaryocytopoiesis. [13][14][15]19 Studies that induced dyshematopoiesis from forced overexpression of Mpl in WT mice demonstrate that TPO effects are tightly regulated by the location and level of Mpl expression. 21,24 At the present time, stem cell transplantation is the only modality available to cure CAMT, which is an otherwise lethal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most of Mpl is expressed on platelets and megakaryocytes, plasma TPO levels fluctuate in response to the physiologic demand for megakaryocytopoiesis. [13][14][15]19 Studies that induced dyshematopoiesis from forced overexpression of Mpl in WT mice demonstrate that TPO effects are tightly regulated by the location and level of Mpl expression. 21,24 At the present time, stem cell transplantation is the only modality available to cure CAMT, which is an otherwise lethal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because TPO is internalized and destroyed after binding to Mpl, plasma TPO levels are primarily regulated by megakaryocyte and platelet mass. [13][14][15][16][17][18][19][20] In murine hematopoietic stem cell gene transfer studies, ectopic expression of an Mpl transgene under the direction of a constitutive promoter produced dyshematopoieses with both inappropriate expansion of erythroid cells and the development of thrombocytopenia due to depressed plasma TPO levels. [21][22][23][24] Successful gene therapy of CAMT necessitates ectopic expression of Mpl in a manner that faithfully mimics its pattern in nature.…”
Section: Introductionmentioning
confidence: 99%
“…In our paper, 1 we demonstrated that the platelet mass directly regulates serum thrombopoietin (TPO) levels by receptor-mediated absorption. We are pleased to know that level in one of their patients with platelet count of 43 × 10 9 /1 was equal to or higher than the Tpo levels in patients with much lower platelet counts (Shinjo, Table 1).…”
Section: To the Editormentioning
confidence: 96%
“…In a recent article in Leukemia Shinjo et al 1 described an inverse correlation between serum thrombopoietin (Tpo) levels and platelet counts in acute leukemia patients with severe chemotherapy-induced thrombocytopenia. They also described an increased binding of Tpo by platelets derived from thrombocytopenic patients, and their overall results thus suggest that the platelet mass directly regulates serum Tpo levels.…”
Section: To the Editormentioning
confidence: 99%
“…In our paper, 1 we demonstrated that the platelet mass directly regulates serum thrombopoietin (TPO) levels by receptor-mediated absorption. We are pleased to know that /1 was equal to or higher than the Tpo levels in patients with much lower platelet counts (Shinjo, Table 1).…”
Section: To the Editormentioning
confidence: 99%